Islam and Its Sacred Book Origin - Yedgina, G.T. (Вестник Карагандинского университета, 2015)
Over the past decade, Kazakhstan's public life has undergone great changes in the public consciousness there is a new life, revived the great traditions, reflecting in particular the spiritual world. Since then, Kazakhstan became a sovereign state and Islamic culture has a very important place in public life. In the context of globalization, the establishment of harmonious relations between different nations, ethnic groups and religious confessions, preserving the unity and confrontation expansive external influences, problems of careful attitude to national, ethnic, and human spiritual values are the actual problem, and Islamic culture plays an irreplaceable role in its solution.
Исламның жəне оның қасиетті кітабінің пайда болуы
Происхождение ислама и его священной книги
Keywords: Islam; culture; loanwords; religion; language; Kazakh; Arabic; Koran; Kazakhstan; history